Microencapsulation of waste sunflower oil as natural self-healing corrosion agent for coating applications - Baharom, Zulkhibri (2021)
Corrosion is a material's destructive attack in reaction to its environment. The extreme consequences of corrosion have become a worldwide issue. Corrosion triggers plant shutdowns, waste of productive energy, loss of product pollution, decrease of productivity and expensive maintenance due to this type of degradation. The effect of the physicochemical interaction due to corrosion can also endanger human safety and generates global issues and economic loss. Microencapsulation is defined as wall formation process where urea formaldehyde (UF) is attached with emulsified waste sunflower oil (WSO) to form a microcapsule. The microcapsules containing WSO were used as smart material to be embedded in epoxy coating known as self-healing coating which can be applied to mild steel. The self-healing coating is used to prevent corrosion that induced by the existence of micro-crack on the coating surface. The WSO was aimed to be encapsulated via in-situ polymerization method with main parameter of stirring speed, reaction time and surfactant concentration. The microencapsulated WSO was characterized by using Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray (EDX) and Fourier Transform Infra-Red Spectroscopy (FTIR). The rare coating technique called sandwich method is used in this study. MS3E5R3 (microcapsules with 300 rpm stirring speed, 5 wt%. of Ethylene Maleic Anhydride, EMA and 3 h reaction time) showed an optimum result of microencapsulation of WSO with smooth and spherical structure of 46 % of yield of microcapsules (Y), 48 % of microencapsulation efficiency (ME) and 66 % of core content (CC). The scratch on the coating matrix autonomously healed after five days and the corrosion rate was also reduced. CS3E5R3 (coating with 300 rpm stirring speed, 5 wt%. of Ethylene Maleic Anhydride, EMA and 3 h reaction time) showed the optimum result of self-healing performance and mechanical strength with 1.47 mm coating thickness, fully healed of healing category, 654.25 N/mm2 maximum stress on bending adhesion test, 6.14 HV of hardness and 83 μm of detachment length on scratch adhesion test. The coating matrix that containing WSO also showed the anti-corrosion ability. CS3E5R3 showed the optimum result of anti-corrosion ability with the lowest mass loss (0.02062 g), corrosion rate (0.0574 mm/yr). The corrosion rate of CS3E5R3 compared to reference sample showed 57 % reduction of rate. The unique morphology of corroded mild steel named lepidocrocite is the novel finding that has not been presented by any researcher involve in the investigation of selfhealing coating. This study revealed that the WSO as a new self-healing corrosion agent is viable self-healing corrosion agent to be microencapsulated. It can be concluded that microcapsules synthesized from a natural agent incorporated with recycling of waste oil could be very auspicious smart coating materials and beneficial for the advancement of corrosion control technology.